1999
DOI: 10.1128/aem.65.5.1924-1929.1999
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Intervention Treatments Resulting in 5-Log 10 -Unit Reductions in Numbers of Escherichia coli O157:H7 and Salmonella typhimurium DT104 Organisms in Apple Cider

Abstract: The U.S. Food and Drug Administration (FDA) recently mandated a warning statement on packaged fruit juices not treated to reduce target pathogen populations by 5 log10 units. This study describes combinations of intervention treatments that reduced concentrations of mixtures of Escherichia coli O157:H7 (strains ATCC 43895, C7927, and USDA-FSIS-380-94) or Salmonella typhimuriumDT104 (DT104b, U302, and DT104) by 5 log10 units in apple cider with a pH of 3.3, 3.7, and 4.1. Treatments used were short-term storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Strawberry juice was diluted, sterilized, and inoculated with bacterial culture as described previously. Twenty-five milliliters of the inoculated juice were dispensed into 100 mL sterile glass bottles and subjected to a freeze-thaw treatment described by Uljas and Ingham (1999) with some adjustments: freezing at −23 • C for 24 or 48 h followed by thawing at 7 ± 1 • C for 4 h. The juices were then stored at 7 ± 1 • C for microbial testing. The total storage time was 8 d by including the 24 and 48 h freezing times.…”
Section: Freeze-thaw Treatment Against E Coli and S Enteritidis In mentioning
confidence: 91%
“…Strawberry juice was diluted, sterilized, and inoculated with bacterial culture as described previously. Twenty-five milliliters of the inoculated juice were dispensed into 100 mL sterile glass bottles and subjected to a freeze-thaw treatment described by Uljas and Ingham (1999) with some adjustments: freezing at −23 • C for 24 or 48 h followed by thawing at 7 ± 1 • C for 4 h. The juices were then stored at 7 ± 1 • C for microbial testing. The total storage time was 8 d by including the 24 and 48 h freezing times.…”
Section: Freeze-thaw Treatment Against E Coli and S Enteritidis In mentioning
confidence: 91%
“…Malic acid, sodium benzoate, potassium sorbate, and their combinations significantly reduced the D (decimal reduction time) value of E. coli O157:H7 in apple cider (Dock and others 2000;Steenstrup and Floros 2002). Uljas and Ingham (1999) showed that combinations of short-term storage at 4, 25, or 35°C, freeze-thawing (48 h at -20°C and 4 h at 4°C), and organic acids (0.1% lactic acid, sorbic acid, and propionic acid) achieved a 5-log reduction in E. coli O157:H7 in apple cider.…”
Section: Introductionmentioning
confidence: 99%
“…In Wisconsin, only a few cider mills (3%) owned equipment for UV-light treatment of cider. Preservatives commonly added to cider, sodium benzoate or potassium sorbate, may have only a small initial effect on survival of E. coli 0157:H7 in refrigerated cider (Miller and Kaspar 1994;Zhao et al 1993), but their effectiveness has been shown to increase when used in combination over a period of several days (Zhao et al 1993) or in combination with prior short-term warm storage and/or freezinghawing of cider (Uljas and Ingham 1999). Preservatives were used by 18% of the cider mills (30% of total cider produced in WI), with potassium sorbate (63%) used more often than sodium benzoate (37%).…”
Section: Preservation Of Cidermentioning
confidence: 99%
“…Of all Wisconsin cider mills surveyed, 15% froze 1549% of their cider, and 22% of mills froze more than one half of their cider. Freezing and thawing can reduce populations of E. coli 0157:H7 in cider (Sage and Ingham 1998) and the potential for a freezehhaw cycle in contributing to a 5 log-unit reduction in pathogen cell numbers when used in combination with short-term warm storage and/or addition of preservatives has been demonstrated (Uljas and Ingham 1999). The results showed that 31% of the total cider produced in Wisconsin was manufactured without pasteurization, UV-light treatment, preservatives, or an implemented HACCP system.…”
Section: Preservation Of Cidermentioning
confidence: 99%
See 1 more Smart Citation